Effect of Different Protocols of Fixed-Time Artificial Insemination on Mucus, Ovarian Size, and Pregnancy of Mixed-Breed Cows in the Humid Tropics of Peru - Clavel Diaz-Quevedo; Alonso Ramírez García; Lenin Torres Bernal; Jorge Cáceres Coral; Gustavo Ampuero Trigoso; José Américo Saucedo-Uriarte (Veterinary Medicine International, 2023)
The objective of the research was to evaluate three synchronization protocols for fixed-time artificial insemination (FTAI) in Bos indicus with Bos taurus crossbred cows. Forty-five cows of 5 ± 1.6 years were selected. The Jsynch treatment consisted of the application of an intravaginal device plus benzoate; on day 8, the device was removed and PGF2α, estradiol cypionate plus eCG was applied, and the FTAI was performed at 48–52 hours after. Conventional treatment consisted of the application of an intravaginal device plus benzoate; on day 8, the device was removed and PGF2α plus eCG was injected, and on day 9, estradiol benzoate was administered, and FTAI was performed at 30 hours. The Ovsynch treatment consisted of the application of GnRH, and on day 8, PGF2α was applied, on day 9, GnRH was applied again, and on day 10, FTAI plus GnRH was applied. The diagnosis of pregnancy was determined by transrectal ultrasound 45 days after the FTAI. The Jsynch (39.1%) and conventional (39.1%) treatment showed higher pregnancy compared to the Ovsynch treatment (21.7%) of pregnancy. The presence of crystalline mucus at the time of the FTAI was significantly associated with pregnancy. The results of this investigation indicate that it is possible to obtain acceptable pregnancy rates with the FTAI in B. indicus with B. taurus crossbred milk-producing cows, and treatments with progesterone-releasing devices plus eCG can improve the reproductive performance of cows.